The -117 mutation in Greek HPFH affects the binding of three nuclear factors to the CCAAT region of the gamma-globin gene. - Superti-Furga, G (1988)
The Greek form of hereditary persistence of fetal hemoglobin (HPFH) is associated with a point mutation immediately upstream of the distal of the two CCAAT elements of the A gamma-globin gene. Three proteins present in nuclear extracts of erythroleukemia cells bind to this CCAAT region and contact the nucleotide mutated in Greek HPFH. The ubiquitous CCAAT-binding factor CP1 interacts preferentially with the proximal CCAAT sequence. An erythroid cell-specific factor, referred to as NF-E, binds with a higher affinity to the distal CCAAT region and interacts only with sequences flanking the CCAAT motif. The third protein is the vertebrate homologue of the sea urchin CCAAT displacement protein and recognizes sequences in both CCAAT elements and their flanking sequences. While the point mutation in Greek HPFH slightly strengthens the binding of CP1 and the CCAAT displacement protein, the same base change strongly reduces the binding of NF-E to the distal CCAAT region, suggesting a possible role of NF-E in the repression of gamma-globin genes in adult erythroid cells.